Dímeros Cíclicos de derivados do ácido metanóico: um estudo computacional de propriedades moleculares, topológicas e do efeito cooperativo. - Maia Neto, José Alberto (2015)
The main objective of this study is to elucidate the cooperative effect caused by the formation of dimers of carboxylic acids, R-COOH, with R= -H, -CH3 e –OH, by the formation of two intermolecular hydrogen bonds. In order to complement the study of cooperative effect, changes in structural, electronic, vibrational and topological of the species involved due to the intermolecular interaction were analyzed. The quantum-computational methods employed were MP2 and DFT/B3LYP, both together with the base 6-311++G(d,p). The QTAIM and NBO methods were used to assess the topology of the electron density and the greatest contribution to the orbital intermolecular interaction, respectively. The results showed no significant differences between the two methods correlated, leading us to suggest the use of DFT / B3LYP method to study similar systems to the investigated here due to their lower computational requirements. The increment values in bond length of the proton donor group are enhanced in dimers R = -CH3 in both calculating levels. The values of intermolecular bond length in dimers R = -OH were the smallest observed in both MP2 and DFT / B3LYP methods. The carboxylic acids dimers with R = -CH3 were the most stabilized by the formation of hydrogen bonds. Regarded to the harmonic effect redshift stretching mode of proton donating groups to carboxylic acids, they were well pronounced and could be observed in all dimers. The new vibrational modes were also pronounced, emphasizing the stretch of the intermolecular bond method. From the studies employing QTAIM was possible to obtain the values of the electron density and the Laplacian of the electron density and evaluate these parameters at critical points in OH bond and intermolecular hydrogen bond, demonstrating the formation of hydrogen dimers. With studies employing the NBO method were evaluated pair of orbital occupancy variations not shared electrons of oxygen (proton donor) and the interaction energy of the orbital involved in intermolecular hydrogen bond.